2020
DOI: 10.1177/0021998320918015
|View full text |Cite
|
Sign up to set email alerts
|

Computational micromechanics-based prediction of the failure of unidirectional composite lamina subjected to transverse and in-plane shear stress states

Abstract: This paper presents a micromechanics-based 3D finite element model for predicting the damage initiation, propagation, and failure strength of TC33/Epoxy carbon fiber reinforced polymer (CFRP) unidirectional lamina under biaxial loadings. The finite element model is generated by introducing representative volume element (RVE) with a random distribution of fibers and a non-zero thickness, numerically identified interface phase via cohesive elements. In the finite element model, the carbon fibers are considered a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 54 publications
1
30
0
Order By: Relevance
“…Fig. 1 The graphical user interface (GUI) of the plug-in components is desired, so the off-diagonal terms in the elasticity matrix are set to be zero and the stiffness in the two shear directions are assumed to be equal [1,33] The plug-in imposes Periodic Boundary Conditions (PBC) on the corresponding surfaces of the unit cell to ensure the compatibility of strain and stress at the macroscale level. These consist of a series of constraints in which the deformation of each pair of nodes on the opposite surfaces of the unit cell is subject to the same amount of displacements.…”
Section: Main Plug-in Guimentioning
confidence: 99%
See 1 more Smart Citation
“…Fig. 1 The graphical user interface (GUI) of the plug-in components is desired, so the off-diagonal terms in the elasticity matrix are set to be zero and the stiffness in the two shear directions are assumed to be equal [1,33] The plug-in imposes Periodic Boundary Conditions (PBC) on the corresponding surfaces of the unit cell to ensure the compatibility of strain and stress at the macroscale level. These consist of a series of constraints in which the deformation of each pair of nodes on the opposite surfaces of the unit cell is subject to the same amount of displacements.…”
Section: Main Plug-in Guimentioning
confidence: 99%
“…With the development of computing capacities, numerical methods, in particular the finite element method (FEM), have become widely used tools for studying the behaviour of composites, including inverse analysis [8,15,26], elastic moduli [27], failure of composite lamina [29,33,34], and the effective coefficients of thermal expansion [13]. Inverse analysis has been used to identify fibre mechanical properties and fibre thermal expansion coefficient, and evaluate the factors of analytical methods, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…The physical meaning of strength ratio R is safety factor, and higher strength ratio corresponds to higher safety margin. The Tasi-Wu strength failure criterion, which is widely used in the field of composite materials [28]- [30], is selected to examine the strength of the composite leaf springs. The single-layer strength ratio of composite materials can be…”
Section: Strength Analysis Of the Composite Leaf Spring Under The Constraint Of The Stiffnessmentioning
confidence: 99%
“…They concluded that a model size containing 30 to 50 fibers is sufficient to represent the homogenized behavior. Sharma and Daggumati [ 7 ], Liu and Li [ 8 ], and Wan et al [ 9 ] investigated the initial failure location and damage evolution under transverse loading. The works of Yan and Ran [ 10 ], Asp et al [ 11 ], Hobbiebrunken et al [ 12 ], and Moraleda et al [ 13 ] investigate the effect of the strength of the interface on the damage evolution.…”
Section: Introductionmentioning
confidence: 99%